Handbook for Communicating Travel Time Reliability Through Graphics and Tables - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report: Handbook for Communicating Travel Time Reliability Through Graphics and Tables offers ideas on how to communicate reliability information in graphical and tabular form.SHRP 2 Reliability Project L02 has also released Establishing Monitoring Programs for Travel Time Reliability, which describes what reliability is and how it can be measured and analyzed, and Guide to Establishing Monitoring Programs for Travel Time Reliability, which describes how to develop and use a Travel Time Reliability Monitoring System (TTRMS).
Keywords: Transportation and Infrastructure

Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 767: Measuring and Removing Dissolved Metals from Stormwater in Highly Urbanized Areas presents prototype best management practices (BMPs) for the removal of dissolved metals in stormwater runoff.The report presents three conceptual configurations in detail: two vault system configurations for urban and rural settings, and an inlet scupper with media for bridge deck drainage systems.The report also includes standard protocols to accurately measure the levels of dissolved metals in stormwater. Practical guidance on the use of these protocols is provided in an appendix to the final report. The report is accompanied by an Excel spreadsheet on CD designed to assist in sizing the filter bed in the vaults and the bridge deck inlet scupper.The CD is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD from an ISO image are provided below.Help on Burning an .ISO CD ImageDownload the .ISO CD ImageCD Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Understanding Microbial Biofilms in Receiving Waters Impacted by Airport Deicing Activities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Report 115: Understanding Microbial Biofilms in Receiving Waters Impacted by Airport Deicing Activities provides an introduction to the factors than can affect biofilm growth sometimes observed in streams that receive airport runoff containing deicers.
Keywords: Transportation and Infrastructure

Non-Nuclear Methods for Compaction Control of Unbound Materials - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 456: Non-Nuclear Methods for Compaction Control of Unbound Materials documents information on national and international experience with non-nuclear devices and methods for measuring compaction of unbound materials.
Keywords: Transportation and Infrastructure

Analysis of Naturalistic Driving Study Data: Safer Glances, Driver Inattention, and Crash Risk - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-S08A-RW-1: Analysis of Naturalistic Driving Study Data: Safer Glances, Driver Inattention, and Crash Risk explores the relationship between driver inattention and crash risk in lead-vehicle precrash scenarios (corresponding to rear-end crashes).
Keywords: Transportation and Infrastructure

Synthesis of Information Related to Transit Problems: 2014 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 108: Synthesis of Information Related to Transit Problems is a digest of the progress and status of TCRP Project J-7, “Synthesis of Information Related to Transit Problems,” for which the Transportation Research Board is the agency conducting the research.
Keywords: Transportation and Infrastructure

Characterization of Cementitiously Stabilized Layers for Use in Pavement Design and Analysis - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 789: Characterization of Cementitiously Stabilized Layers for Use in Pavement Design and Analysis presents performance-related procedures for characterizing cementitiously stabilized layers for incorporation into mechanistic–empirical pavement analysis methods. Appendices to the report are available online.
Keywords: Transportation and Infrastructure

Research and Technology Coordinating Committee Letter Report: January 2015 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
A January 21, 2015 letter report from TRB's Research and Technology Coordinating Committee (RTCC) to the U.S. Federal Highway Administration (FHWA) offers recommendations related to project evaluation in the Office of Research, Development, and Technology (RD&T) and communicating the value of RD&T.The RTCC’s charge is to monitor and review FHWA’s research and technology activities; advise FHWA on setting a research agenda and coordination of highway research with states, universities, and other partners; review strategies to accelerate the deployment and adoption of innovation; and identify areas where research may be needed. RTCC’s review includes the process of research agenda setting; stakeholder involvement; and the conduct of research, peer review, and deployment. The committee’s role is to provide strategic, policy-level advice on topical priorities, processes, and strategies to accelerate the adoption of innovation.The letter report recommends that FHWA run one project all the way through the agency’s project evaluation process to demonstrate its approach and develop a model for further project evaluations in the future; and take a more strategic approach to its communication efforts by targeting information to the interests and concerns of specific audiences.
Keywords: Transportation and Infrastructure

Effective Cooperation Among Airports and Local and Regional Emergency Management Agencies for Disaster Preparedness and Response - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 50: Effective Cooperation Among Airports and Local and Regional Emergency Management Agencies for Disaster Preparedness and Response focuses on how airports and their emergency management partners establish and sustain effective working relationships, and methods of identifying problems and rebuilding damaged relationships.The report is designed to provide airports and their emergency response allies access to a full range of policies, programs, practices, and relationships for establishing and sustaining good working relationships.
Keywords: Transportation and Infrastructure

Development of Tools for Assessing Wider Economic Benefits of Transportation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) S2-C11-RW-1: Development of Tools for Assessing Wider Economic Benefits of Transportation describes spreadsheet-based tools designed to help calculate a transportation project's impact on travel time reliability, market access, and intermodal connectivity.The report includes an accounting system designed to incorporate the three metrics into economic benefit and economic impact analyses.Disclaimer: This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Maintaining Transit Effectiveness Under Major Financial Constraints - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Synthesis 112: Maintaining Transit Effectiveness Under Major Financial Constraints discusses transit agencies that implemented plans to increase their cost effectiveness and how the agencies communicated with their communities during challenging fiscal circumstances.
Keywords: Transportation and Infrastructure

Best Practices for General Aviation Aircraft Fuel-Tank Sampling - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 21: Best Practices for General Aviation Aircraft Fuel-Tank Sampling estimates the discard amounts from fuel testing samples that are entering the stormwater run-off system, and develops best practices for proper disposal of the fuel-tank samples.
Keywords: Transportation and Infrastructure

Long-Term Performance and Life-Cycle Costs of Stormwater Best Management Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 792: Long-Term Performance and Life-Cycle Costs of Stormwater Best Management Practices provides tools and guidance to help optimize the best management practices (BMP) portion of a transportation department’s stormwater program. The report is accompanied by a CD-ROM containing a BMP evaluation tool in a spreadsheet format as a computational aid that provides average annual performance and whole life costs for treatment BMPs.The CD-ROM is also available for download from TRB’s website as an ISO image. Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

Improving Transit Integration Among Multiple Providers, Volume I: Transit Integration Manual - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Report 173: Improving Transit Integration Among Multiple Providers, Volume I: Transit Integration Manual provides guidelines and procedures to assist transit agencies in evaluating, planning, and implementing steps to integrate transit services in areas with multiple transit providers.This report accompanies TCRP Report 173, Volume II: Research Report. Together, these documents demonstrate benefits of transit integration; illustrate the range of potential types of integration activities; and describe procedures necessary to carry out integration efforts, including tips for success.
Keywords: Transportation and Infrastructure

Manager’s Guide to the Integrated Ecological Framework - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) S2-C06-RW-4: Manager’s Guide to the Integrated Ecological Framework is designed to provide a basic understanding of the Integrated Ecological Framework (IEF), a nine-step process for integrating ecological and transportation planning. It presents information about the relevant stakeholders and types of expertise needed to help ensure positive transportation infrastructure and conservation outcomes. The guide also includes updates to earlier documents developed for the C06 project. The guide is available in electronic format only.The guide is part four of a four-volume set. Other volumes in the set include:An Ecological Approach to Integrating Conservation and Highway Planning, Volume 1 summarizes the research approach and major findings of a project designed to help transportation and environmental professionals apply ecological principles early in the planning and programming process of highway capacity improvements to inform later environmental reviews and permitting.An Ecological Approach to Integrating Conservation and Highway Planning, Volume 2 is a summary of the approach and outcomes of a partner project, Integration of Conservation, Highway Planning, and Environmental Permitting through Development of an Outcome-Based Ecosystem-Scale Approach and Corresponding Credit System.The third volume, Practitioner’s Guide to the Integrated Ecological Framework, describes the IEF and outlines a way to integrate the conservation and restoration needs and objectives of multiple entities.A supplemental report, Integrated Ecological Framework Outreach Project, documents the techniques used to disseminate the project's results into practitioner communities and provides technical assistance and guidance to those agencies piloting the products.Each step of the IEF is supported by a database of case studies, data, methods, and tools. The IEF is available through the Transportation for Communities – Advancing Projects through Partnerships (TCAPP) website. TCAPP will be re-launched at a future date as “PlanWorks” by the Federal Highway Administration.
Keywords: Transportation and Infrastructure

Accelerating Implementation of Transportation Research Results - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 461: Accelerating Implementation of Transportation Research Results examines implementation practices used by public-sector nontransportation agencies, nonprofits, and academia to accelerate practical application of research results. The emphasis is on practices that might be useful for transportation agencies to create more responsive research programs.
Keywords: Transportation and Infrastructure

Application of Geospatial Ecological Tools and Data in the Planning and Programming Phases of Delivering New Highway Capacity: Proof of Concept—US-101, California - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Capacity Project C40B has released a report that demonstrates the transferability of previously-developed methods to assess biological and ecological impacts from transportation projects. The report also documents the development of a national impact scoping tool.The C40B project also produced Regulatory Acceptability of Remotely Sensed Data and an additional proof of concept report about the Contra Costa County Transportation Authority.
Keywords: Transportation and Infrastructure

Impact of the Affordable Care Act on Non-Emergency Medical Transportation (NEMT): Assessment for Transit Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s Transit Cooperative Research Program (TCRP) Research Results Digest 109: Impact of the Affordable Care Act on Non-Emergency Medical Transportation (NEMT): Assessment for Transit Agencies assesses the potential impact of implementing the NEMT provision of the Affordable Care Act on a state-by-state basis. The report also collates information to inform the transit community on how public transit and NEMT providers may integrate or use their respective resources and services.
Keywords: Transportation and Infrastructure

A Debris Management Handbook for State and Local DOTs and Departments of Public Works - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 781: A Debris Management Handbook for State and Local DOTs and Departments of Public Works provides debris management practices for local, tribal, and state departments of transportation and for public works agencies. A PowerPoint presentation and a final report describing the methodology of the project are available online.
Keywords: Transportation and Infrastructure

Utility-Locating Technology Development Using Multisensor Platforms - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-R01B-RW-1: Utility-Locating Technology Development Using Multisensor Platforms documents the development of multisensor technologies and geophysical software as applied in underground utility detection and location.SHRP 2 Renewal Projects R01B and R01C developed a report about the testing of the geophysical tools developed in the R01B and R01C projects.
Keywords: Transportation and Infrastructure